The Stages of International Growth of the Business Groups From Emerging Economies - Bugador, Roderick (Organizations and Markets in Emerging Economies, 2015)
The previous studies have focused on weak institutional environment in explaining the growth of business groups in emerging economies. The recent events, however, show that business groups continue to grow even when the institutions are getting better. This is evident both in the domestic and international growth stages. This paper addresses this by providing a group and a firm-level analytical framework as an alternative in examining the international growth of business groups. The focus is putting the institutional environment in the background and the business groups in the forefront. The paper builds on the endogenous growth of business groups and proposes that their persistence, regardless of institutions and level of economy, can be explained not only through their environment but also by the internal dynamics of their organizational structure and group-specific advantages. This proposition is based on the theory of the firm through the combined application of transaction cost economics, resource-based and dynamic capabilities views.
Keywords: business groups; business group advantages; affiliate-level advantages; internationalization; emerging economies; organizational growth